KONTRIBUSI QANUN LKS TERHADAP UMKM SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT KOTA - Yusmalinda Yusmalinda (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study aims to analyze the existence or role of the qanun of Islamic financial institutions (LKS) in increasing the economic level of the people of Langsa City. The economic Sharia policy certainly has an impact on financial management and management, which in turn has an effect on the people's economy. This research is a type of explanatory descriptive research that is looking at the causal relationship that occurs between one factor and another by using qualitative data. Sources of data were obtained from secondary data in the form of journals and official websites of the Aceh government, to enrich the data this paper also uses the results of empirical research by researchers who focus on studying the Islamic economy in Aceh. The study results show that after the implementation of Islamic Financial Institutions in Aceh, all conventional banks do not operate in Aceh. The implementation of the LKS Qanun in Aceh has had an influence on the number of funds channeled to MSMEs. However, it has not been able to improve the welfare of the people of Aceh.